Fire safety engineering. (Chartered Institution of Building Services Engineers, 2019)
Fire safety engineering can mean many things to many people, and covers a wide range of levels of knowledge and competence as well as a diverse range of activities. The objective of this Guide is to present a package of measures which will reduce the potential for injury, death, property and financial loss to an acceptable level. A concerted effort has been made to provide information within this Guide that can be used internationally. These references include codes, standards and guidance from the USA that are frequently used in the Middle East and Asia. Fire safety engineering is a continually developing art and science, and users are advised to maintain a personal regime of professional development and to make use of new standards and techniques on an ongoing basis.
Keywords: Fire protection engineering.; elektronické knihy; electronic books